Optimization of Web-based Bill of Lading Document Issuance Mechanism to Improve PT. Container Maritime Activities Jakarta - Marihot Simanjuntak; April Gunawan Malau; Larsen Barasa (International Review of Management and Marketing, 2019)
Dominant containers are used in export and import shipping systems throughout the world accompanied by important documents as a means of proving the realization of a transaction. PT Container Maritime Activities have targets in a Bill Of Lading document publishing, but in fact the Bill of Lading documents are still many who do not pitch e alisasi. In this study, researchers took the problem by using a quantitative approach with descriptive statistical analysis, a method related to the presentation of data (mean, median, mode). From the results of the study there were two indicators of employee competency that were declared weak, and it was a problem that the publication of Bill of Lading documents was not realized. To make optimal Bill of Lading documents in accordance with achievement targets, each employee competency indicator must be declared strong.